KONSTRUKSI ARBEIT DALAM SASTRA JERMAN PASCAREUNIFIKASI - Syamsu Rijal (SASDAYA: Gadjah Mada Journal of Humanities, 2016)
Simultaneous post-reunification with the presence of the New Economy era has brought Germany entered a new phase, especially in the economic field (read: Arbeit). The manufacturing sector which previously controlled the labor market in Germany has been shifted by the services sector (Dienstsleistungsbereiche). Utilization of the latest technology and the power of innovation become key to success. This had an impact on the changing structure of work world (Strukturwandel der Arbeitswelt) in Germany. In this era, Arbeit has been transformed into "charm" (Fetisch)  in the community. Each individual -even who had higher education qualifications- cannot escape the Arbeit problem. Those who lost Arbeit would feel outcast and marginalized, whereas those who worked would be imprisoned in their work. Reality and the dilemma were captured in the novel Das Jahr der Wunder by Reiner Merkel (2001), wir nicht schlafen Kathrin by Röggla (2004), and Mobbing by Annette Pehnt (2007) as corpus research. Thus, the Arbeit conception that has been considered established in a modern country such as Germany is still questioned. So, how about the actual Arbeit construction that is readable in all three of the novel as a form of intrinsic relationship between literature and their communities in the form of negation, innovation and affirmation.